The awareness of smoking effect among youth at Taman Rajawali / Jairah Jamali - Jamali, Jairah (2008)
This study is conduct to examine awareness of negative effects of smoking among youth at Taman Rajawali. The study covered youth and smokers at Tarnan Rajawali. The youth was being selected from Taman Rajawali Sandakan (Block 1 to 34) during February 2009. Primary data for this research was collected through questionnaire survey.